To determine the equation of the linear function that passes through the points (-1, 4) and (1, 0), we can calculate the slope (m) first using the formula:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Using the points (-1, 4) as \((x_1, y_1)\) and (1, 0) as \((x_2, y_2)\):
\[ m = \frac{0 - 4}{1 - (-1)} = \frac{-4}{2} = -2 \]
Now that we have the slope \(m = -2\), we can use the point-slope form of the equation of a line, which is:
\[ y - y_1 = m(x - x_1) \]
Let's use the point (1, 0):
\[ y - 0 = -2(x - 1) \] \[ y = -2x + 2 \]
Thus, the equation of the line is:
\[ y = -2x + 2 \]
So the correct response is:
y = -2x + 2